Determination of the Northwestern Extensions of the Bai Hassan Field (Daoud Culmination) and Its Geological Relationship with Ismail -1 Area, Northern Iraq - Al-Naemi, Ahmed I. S.; Almufti, Torhan M. (Journal of Petroleum Research and Studies, 2021)
The Ismail-1 is located northwest of the Bai Hassan Field (Daoud Culmination), within the administrative boundaries of the provinces of Kirkuk and Erbil, which was later named Ismail Field. The objective of the research is to determine the geological relationship (structural and reservoir) of the well Ismail-1 with the Bai Hassan Field (Daoud Culmination). Based on geological and reservoir studies and seismic surveys of the region, the first basis of the research was based on the stratigraphy, structural, reservoir and morph structure aspects of this relationship. In the beginning, the serial sequence of the well was reviewed and compared with David’s wells. Then, cross-sections and long sections were drawn through the wells of Ismail-1 and Daoud wells, as well as, the fluid levels dotted on such sections. After that, a structural contour map was drawn on top of Jeribe Formation for the area of well Ismail-1 which is currently known as Ismail Field and part of the Bai Hassan Field (Daoud Culmination), depending on the structural and reservoir data. It was found that the area of the well Ismail-1 is an asymmetrical convex fold, the southwestern flank is more inclined than the northeastern flank, and the Daoud Culmination and the Ismailfold is separated by a narrow saddle. However, depending on the structural contour map of the top of Jeribe Formation (-1325) meters from the mean sea level, the deeper levels of which surround the two Culminations together, the similarity of the reservoir properties and the different levels of fluid in the Daoud Culmination and the area of the Ismail-1, all confirm that they are two separate Culminations of one field. So the so-called Ismail Field can be considered a third Culmination called Ismail Culmination of the Bai Hassan Field. Using topographical maps and satellites data, the morph structure and geomorphological phenomena of the northwestern extensions of the Bai Hassan Field (the area of well Ismail-1) and towards the Quir Field, were studied and the northwestern aerial extensions of about 18 km length and 5 km width were delineated. Thus, the Bai Hassan Field is consisting of three Culminations (from the southeast to the northwest, Kithka, Daoud and Ismail Culminations) with a total length about 50 km.